Seorang penderita leukemia myeloid akut dengan leukemia kutis: laporan kasus - Reza Surahmanto; Ketut Suega (DiscoverSys Inc., 2021)
Background: Acute leukemia can show multiple manifestations of extramedullary tissue and extramedullary involvement is relatively rare. Patients with leukemia cutis usually coexist with systemic leukemia, but sometimes precede involvement of the bone marrow or peripheral blood. In rare instances, cutaneous leukemia can be an early manifestation of systemic disorders.Case: A 61 year old male, Balinese ethnicity, presented with the main complaint of ulcers on the right groin area near the genitals since one month ago, accompanied by fever and weight loss of about 5 kg in one month. Right and left inguinal lymph nodes were enlarged. In the right inguinal area, a solitary ulcer was seen. Laboratory results showed an increase in white blood cells, anemia, and thrombocytopenia. Bone marrow aspiration showed hematopoietic distribution predominantly of the myeloid series and appears to suppress erythroid series and megakaryocytes. The myeloid series consists of 20% positive maturation blast cells without auer rod. The excisional biopsy of the right inguinal ulcer depicts the dermis showed mature and immature granulocyte infiltration. The patient was diagnosed with matured AML (M2) and leukemia cutis. The patient was planned to be given a chemotherapy regimen but the patient developed complications from pneumonia and passed away.Conclusion: A case of 61 years old man has been reported, with complaints of injuries to the right groin near the genitals and fever. The patient was diagnosed with matured acute myeloid leukemia (M2) and leukemia cutis. Leukemia cutis is an extramedullary involvement of leukemia and is of clinical importance. Latar Belakang: Leukemia akut dapat menunjukkan beragam manifestasi pada jaringan ekstramedula dan keterlibatan ekstramedula relatif jarang terjadi. Pasien dengan leukemia kutis biasanya terjadi bersamaan dengan leukemia sistemik, namun terkadang mendahului keterlibatan dari sumsum tulang atau darah tepi. Pada kasus yang jarang, leukemia kutis dapat menjadi manifestasi awal dari kelainan sistemik.Laporan Kasus: Laki-laki 61 tahun, suku Bali, datang dengan keluhan utama borok pada daerah selangkangan kanan dekat dengan kemaluan sejak satu bulan yang lalu. Keluhan juga disertai demam dan penurunan berat badan sekitar 5 kg dalam satu bulan. Pada inguinal kanan dan kiri didapatkan pembesaran kelenjar getah bening. Pada daerah inguinal kanan tampak ulkus soliter. Hasil lab didapatkan peningkatan sel darah putih, anemia, serta trombositopenia. Aspirasi sumsum tulang menunjukkan sebaran hematopoietik yang didominasi seri myeloid dan tampak menekan seri eritroid serta megakaryosit. Seri myeloid terdiri dari sel blast 20% dengan maturasi positif tanpa auer rod. Hasil biopsi eksisi pada ulkus daerah inguinal kanan menggambarkan jaringan yang terdiri dari epidermis dan dermis. Pada dermis tampak infiltrasi granulosit matur dan imatur. Pasien didiagnosis dengan LMA dengan maturasi (M2) dan leukemia kutis. Pasien direncanakan pemberian regimen kemoterapi namun pasien mengalami komplikasi infeksi pneumonia dan meninggal.Simpulan: Telah dilaporkan kasus laki-laki 61 tahun, dengan keluhan luka pada selangkangan kanan dekat kemaluan serta demam. Pasien didiagnosis leukemia myeloid akut dengan maturasi (M2) dan leukemia kutis. Leukemia kutis merupakan keterlibatan ekstramedula dari leukemia dan memiliki arti penting secara klinis.